Information Shadow: How a Company Maintains a Presence Without Working - Liestiev, Yevhen (Global Prosperity, 2025)
The article explores the phenomenon of a company's "information shadow" as a specific form of information presence that is not related to actual operational activities, but keeps the entity in the public space of the market. It analyzes how companies use information resources to maintain their reputation and competitive positions, while exposing the vulnerability of the information field to manipulation.The relevance of the study is due to the growing role of the digital economy, where information acts as a commodity and a tool for shaping market behavior. In the context of increased competition and virtualization of business processes, the phenomenon of the "information shadow" acquires economic significance, affecting reputation, investment attractiveness and consumer trust, which requires deep scientific understanding.The goal is to investigate the mechanism of formation and implementation of a company's "information shadow", assess its motivations, economic goals, and potential risks, as well as develop methodological approaches to identifying this phenomenon.The materials and methods used include multi-channel analysis of the company's public digital footprint, monitoring of social networks, media, business directories, review aggregators and corporate websites. The research is based on content analysis, comparison of public information with independent sources (registers, court records), as well as assessment of relationships in the digital space through SEO optimization and mentions on third-party resources.The obtained scientific results indicate that the "information shadow" acts as an element of symbolic capital, allowing companies to maintain reputation, retain customers, influence investors and transform the brand into a new asset even in the absence of operational activity. At the same time, risks such as distortion of the competitive environment, consumer disorientation and regulatory violations have been identified, which require analytical monitoring and verification.Prospects for further research focus on developing legal and institutional mechanisms to regulate the "information shadow", implementing standards for verifying digital presence, and creating a new paradigm of economic control that integrates technology, ethics, and analytical flexibility.